More fishers and fewer martens due to cumulative effects of forest management and climate change as evidenced from local knowledge - Pauline Suffice; Hugo Asselin; Louis Imbeau; Marianne Cheveau; Pierre Drapeau (BMC, 2017)
Abstract Background Monitoring of fur-bearing species populations is relatively rare due to their low densities. In addition to catch data, trappers' experience provides information on the ecology and status of the harvested species. Fisher (Pekania pennanti) and American marten (Martes americana) are mustelids that are sensitive to forest management and therefore considered to be ecological indicators of forest health. Fisher populations have increased in eastern North America since the early 2000s and this could have resulted in a northeastern extension of the species' range and increased overlap with marten's range. Moreover, habitats of both species are subject to natural and anthropogenic disturbances. The objective of this study was to document the knowledge held by local trappers in the northern area of sympatry between fisher and marten to identify factors that could explain variation in populations of the two species and interactions between them. Method Forty-one semi-directed interviews with Indigenous and non-Indigenous trappers in the Abitibi-Témiscamingue region of western Quebec (Canada), at the northern limit of the overlapping ranges of the two mustelid species. Results Trappers highlighted the lack of exclusivity of marten and fisher to coniferous forests, although marten is more closely associated with them than is fisher. Fisher apparently also takes advantage of open environments, including agroforestry systems. Moreover, climate change increases the frequency of freeze-thaw events that cause the formation of an ice crust on the snow surface, which favors fisher movements. Conclusion The fisher was identified as a competitor and even a predator of the marten. Furthermore, the fisher is less affected than the marten by forest management, and it also seems to benefit from climate change to a greater extent.